Worthwhile or wasteful? Assessing the need for a radical revision of evaluation in small-sized development NGOs. Issue 2 (17th February 2022) - Kelly, Leanne M.
ABSTRACT: Recent years have heralded an unprecedented push for evaluation of non-government organisation (NGO) programmes. Meanwhile, there has been little consideration of how evaluation expectations affect small-sized development NGOs. Small NGOs contend with several challenges including limited staff skill-pools, stretched time, and insufficient funding. This paper investigates evaluative practices in 20 small development NGOs to examine how they check effectiveness, improve their programmes, and remain accountable to donors and intended beneficiaries in ways that are meaningful and useful to them. These findings suggest the need for radical post-development style conversations to critically rethink evaluation worth, particularly for small NGOs.